EFFORTS TO PREVENT SEXUALLY TRANSMITTED DISEASES IN CLASS IIA BANJARMASIN CORRECTIONAL INSTITUTION - Nugroho, Katon Galih; Biafri, Vivi Silviani (Universitas Nusa Cendana, 2025)
This study aims to explore efforts to prevent sexually transmitted diseases (STDs) in Banjarmasin Class IIA Correctional Institution. The methods used in this study included observation and interviews with prisoners and health workers to gain an in-depth understanding of the health conditions and prevention practices implemented. The results showed that prevention measures taken include initial health checks for new inmates, including health history assessment and HIV testing for those at high risk. In addition, health socialization is conducted through routine programs such as morning exercises to raise awareness of the importance of a healthy lifestyle. Findings also revealed that factors contributing to the transmission of STDs include deviant sexual behavior, institutional overcapacity, and the lack of awareness of prisoners towards their health. This study emphasizes the importance of a holistic approach in addressing health issues in prisons, which focuses not only on treatment but also on health education and counseling as an effective prevention strategy. The results are expected to provide recommendations for prison managers in creating a safer and healthier environment for prisoners. Keywords: Infectious Diseases; Sexual; Correctional Institutions